2000
DOI: 10.1002/(sici)1099-0518(20000601)38:11<1972::aid-pola60>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Organic-inorganic hybrid materials. V. Dynamics and degradation of poly(methyl methacrylate) silica hybrids

Abstract: Poly(methyl methacrylate)–silica hybrid materials (PMMA–SiO2) were prepared by in situ polycondensation of alkoxysilane in the presence of trialkoxysilane‐functional PMMA. Infrared, differential scanning calorimetry, 29Si and 13C nuclear magnetic resonance spectroscopy, and thermogravimetric analysis were used to study the PMMA–SiO2 hybrids. The effects of the content and kind of the alkoxysilane on the dynamics and stability of the PMMA–SiO2 hybrids were investigated in this study.The dynamics of SiO2within h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 30 publications
6
51
0
Order By: Relevance
“…The spectra show six peaks at -50 to -51, -57 to -59, -65 to -67, -91 to -93, -100 to -102, and -109 to -111 ppm (Figure 6A), which are assigned to T 1 , T 2 , T 3 , Q 2 , Q 3 , and Q 4 , respectively. The positions of these peaks are similar to previous reports [29,30]. These peaks correspond to the chemical structures shown in Figure 6B.…”
Section: Characterizationsupporting
confidence: 89%
“…The spectra show six peaks at -50 to -51, -57 to -59, -65 to -67, -91 to -93, -100 to -102, and -109 to -111 ppm (Figure 6A), which are assigned to T 1 , T 2 , T 3 , Q 2 , Q 3 , and Q 4 , respectively. The positions of these peaks are similar to previous reports [29,30]. These peaks correspond to the chemical structures shown in Figure 6B.…”
Section: Characterizationsupporting
confidence: 89%
“…Among inorganic fillers added to PMMA, silica was the most widely investigated. [10][11][12][13][14] The thermal degradation of such composites was a prime areas of investigation. It was shown that the addition of silica into PMMA improves thermal stability of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerization or condensation degree of the trifunctional %Dc(T) and tetrafunctional %Dc(Q) species was calculated using the equations (Equations 3 and 4) [22,24] : ( )…”
Section: Each Tmentioning
confidence: 99%
“…The total fractions of trifunctional and tetrafunctional species were calculated as follows (Equations 5 and 6) [22,24] : The total degree of condensation corresponds to (Equation 7) [22,24] :…”
Section: Each Tmentioning
confidence: 99%